METHODOLOGICAL AND PRAGMATIC CHARACTERISTICS OF UZBEK LANGUAGE CONJUNCTIONS - Usmanov Aslam Karshiboyevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article studies the methodological and pragmatic meaning of conjunctions. Linguistic nature of connectives, its stylistic features and linguopragmatic features are highlighted, scientifically analyzed with the help of examples.